Artesunate-amodiaquine treatment for children with uncomplicated malaria in Kalimantan and Sulawesi: clinical complaints, tolerability and compliance - Retno Gitawati; Ani Isnawati; Emiliana Tjitra; Mariana Raini; Ondri Dwi Sampurno; Indri Rooslamiati (Paediatrica Indonesiana, 2012)
Background Artesunate-amodiaquine combination (AS+ AQ)is one type of artemisinin-based combination therapy (ACT) andhas been used in Indonesia since 2004 for uncomplicated malaria,both in adults and children. However, its use in the IndonesiaMalaria Program has not yet been evaluated.Objective To evaluate the clinical complaints and tolerabilityto AS+AQ treatment, as well as compliance in children withuncomplicated malaria.Methods This was a cross-sectional study, conducted in sentinelpuskesmas (primary health centers) in Kalimantan and Sulawesi.Subjects were 126 children aged under 15 years, with P. falciparum,P. vivax, or mixed falciparum-vivax malaria infections. All subjectswere treated with a single dose of AS+AQ for three consecutivedays and followed-up 3 times (D3, D7 and D28) to record clinicalcomplaints and tolerability after drug administration. Parents/guardians underwent in-depth interviews on the knowledge,attitudes and practices of the ACT used as well as clinicalcomplaints following AS+ AQ treatment.Results Of the 126 subjects evaluated, 30 were infected with P.falciparum, 5 9 with P. vivax, and 3 7 with both species. About 84% ofthe subjects reported clinical complaints after AS+ AQ administration(DO-DZ), most commonly lethargy, nausea and vomiting, similar tothe clinical symptoms of malaria. All complaints were reported to bemild and tolerable. Only one subject was lost to follow-up.Conclusion Clinical complaints experienced by malaria-infectedchildren following AS+AQ treatment were relatively tolerable.Subjects' compliance to AS+ AQ treatment was satisfactory.[Paediatr lndones. 2012;52:10-5).